2010
DOI: 10.1155/2011/457079
|View full text |Cite
|
Sign up to set email alerts
|

Kainic Acid‐Induced Neurodegenerative Model: Potentials and Limitations

Abstract: Excitotoxicity is considered to be an important mechanism involved in various neurodegenerative diseases in the central nervous system (CNS) such as Alzheimer's disease (AD). However, the mechanism by which excitotoxicity is implicated in neurodegenerative disorders remains unclear. Kainic acid (KA) is an epileptogenic and neuroexcitotoxic agent by acting on specific kainate receptors (KARs) in the CNS. KA has been extensively used as a specific agonist for ionotrophic glutamate receptors (iGluRs), for example… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(74 citation statements)
references
References 118 publications
3
69
0
Order By: Relevance
“…In addition to investigating the role that loss of EGFR has with traumatic brain injury we wanted to determine if EGFR ablated brains are susceptible to neurotoxicity‐induced neuronal death. One model routinely used to investigate such phenomenon is the triggering of seizures with Kainic acid (KA), a marine‐derived amino acid that has a very high activating potential of glutamate transporters 38, 39, 40, 41. Several molecules acting downstream of the EGFR have been implicated in mediating KA‐induced neurotoxicity 42, 43.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to investigating the role that loss of EGFR has with traumatic brain injury we wanted to determine if EGFR ablated brains are susceptible to neurotoxicity‐induced neuronal death. One model routinely used to investigate such phenomenon is the triggering of seizures with Kainic acid (KA), a marine‐derived amino acid that has a very high activating potential of glutamate transporters 38, 39, 40, 41. Several molecules acting downstream of the EGFR have been implicated in mediating KA‐induced neurotoxicity 42, 43.…”
Section: Resultsmentioning
confidence: 99%
“…Excitotoxicity is the pathological process where neurons are damaged or killed by overstimulation of glutamate receptors in the Central Nervous System (CNS) by excitatory amino acids and it is considered to be contributing factor in the pathogenesis of various neurodegenerative disorders in the CNS (Wang, et al, 2005;Zhu, 2011, Zheng, et al, 2011). It was earlier reported that stimulation of glutamate-KA receptors induces neuronal NO release, which in turn modulates glutamate transmission (Alabadi et al, 1999;Nakaki etal., 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Kainic acid (KA), an agonist for the iGluR subtype which is known as a non-degradable analog of the excitotoxin, glutamate, offers a well-characterized model for the study of NDDs (Wang et al, 2005; Zhang et al, 2010; Zheng et al, 2010). DomA, a naturally occurring marine neurotoxin produced by members of the diatom genus, Pseudo-nitzschia , is a structural relative of KA (Lu et al, 2013).…”
Section: Glutamate Receptors As Potential Targets In Neurotoxic Agentmentioning
confidence: 99%